Strategi Pengembangan UMKM Kuliner dengan Peran NIB dan Sertifikasi Halal dalam Memperluas Pasar di Desa Sraten - Lorenza Jufri; Hani Pritananda Anisasiwi; Fannysha Septiani; Intan Azaly; Najib Haidi Lutfillah; Nabila Azzahrah; Muhammad Amar Hanif; Taqiyah Nurul ‘Azzah; Mujiyati Mujiyati (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
Micro, Small, and Medium Enterprises (MSMEs) in Sraten Village are not yet aware of the importance of business legality due to a lack of knowledge about business permits that are useful for expanding the market for MSMEs in Sraten Village. This activity aims to raise awareness among MSME actors in Sraten Village about the importance of business legality, such as the Business Identification Number (NIB) and halal certification, in order to expand the market and enhance competitiveness. Based on observations, it was found that many MSME actors in the village still do not understand the importance of business legality. To address this issue, socialization and assistance were provided in the registration of NIB using the OSS system. As a result, 28 business actors in the culinary field successfully registered and obtained their NIB. Additionally, halal certification was introduced to enhance consumer trust and expand access to the global halal market. Through this education, MSME actors are expected to better understand and utilize business legality for the development of their businesses. This activity concluded with a seminar featuring speakers to deepen the understanding of business actors regarding legality and halal certification.